Behavioral Analyses in Dark Agouti Rats Following Repeated Systemic Treatment With Fingolimod (FTY720) - Marie Jakobs; Lisa Trautmann; Martin Hadamitzky; Julia Bihorac; Lucie Jacquet; Uwe Christians; Björn Schniedewind; Laura Lückemann; Manfred Schedlowski (Brain and Behavior)
ABSTRACT Background Studies in experimental animals revealed that acute and chronic treatment with small‐molecule immunosuppressive drugs lead to neurobehavioral alterations in rodents. Methods Against this background, this study investigated behavioral alterations in rats after repeated administration of FTY720, an immunosuppressive drug used for the treatment of multiple sclerosis, employing the open field, elevated plus maze, and dark/light tests. Results Compared to controls, repeated FTY720 treatment affected behavior in rats, reflected by a reduction in distance traveled as well as increased time engaged in freezing in the open field and elevated plus maze. Furthermore, the time spent freezing in the elevated plus maze test positively correlated with FTY720 concentrations in the amygdala and insular cortex, two brain regions involved in regulation of emotionality. Since no changes in plasma corticosterone levels were observed, stress effects due to treatment, behavioral testing, or handling can be ruled out. Conclusion The present findings indicate that treatment with FTY720 did not induce typical anxiety‐like behavioral patterns in otherwise healthy rats as seen following treatment with other immunosuppressive drugs. Nevertheless, it remains of great importance to evaluate behavioral effects in clinical practice to shed more light onto possible detrimental side effects emerging during treatment with small‐molecule immunosuppressive drugs.